An overview of the relationship between juvenile idiopathic arthritis and potential environmental risk factors: Do early childhood habits or habitat play a role in the affair? - Köker, Oya (My University, 2022)
Aim The current study was undertaken to evaluate the influence of breastfeeding on the development and outcome measures of juvenile idiopathic arthritis (JIA). The second aim was to determine the consequences of particular sociodemographic and sociocultural characteristics and nutritional behavior of early childhood on JIA. Methods The study includes the patients diagnosed with JIA and regularly followed up at the Department of Pediatric Rheumatology in Istanbul University-Cerrahpasa. The comparison group consisted of healthy subjects and patients with juvenile systemic lupus erythematosus (jSLE). A face-to-face survey method was conducted with the parents of the participants between February 1, 2021, and September 1, 2021. Results The mean age of the JIA cohort (n = 324) was 12.2 +/- 4.7 years, with a female ratio of 64.8%. The breastfeeding rate differed from the control groups (253 healthy subjects and 88 patients with jSLE) but was higher with a value of 94.8%. There was no difference between the groups (P = .097, P = .064) or within the subgroups of JIA (P = .12) regarding breastfeeding duration. Cow\"s milk introduction time (P = .02, P = .0001), household pet-keeping (P = .001), income level (P = .0001), maternal literacy (P = 0.013) made a statistical difference vs the control groups. Conclusion No relationship was established between the rate or duration of breastfeeding and the development or severity of JIA. The early introduction of cow\"s milk was found to be higher in the patient cohorts. The income level and maternal literacy appeared to be relevant with the high disability and damage scores, and frequent relapse rates. Secondhand smoking, higher in JIA, may prompt the basis of primary preventable strategies in JIA.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; breastfeeding; early childhood exposures; environmental factors; juvenile idiopathic arthritis; outcome